DIGITAL MARKETING DI OBJEK WISATA KOPU RAFTING DESA TANJUNG KECAMATAN KOTO KAMPAR HULU - Yumni, Cindi Ulfa; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Indonesia is one of the countries that takes advantage of the tourism industry, because it has so many charms that can be enjoyed. One of the potential tourist destinations in Kampar Regency is the Kopu Rafting tourist attraction which is located in Tanjung village, Koto Kampar Hulu District, Riau Province. This research aims to determine the implementation of digital marketing at the Kopu Rafting tourist attraction in Tanjung village, Koto Kampar Hulu District in attracting visitor interest. This research uses a descriptive qualitative method which aims to share a description of a social sign that is researched in depth. Researchers define a sign based on the atmosphere and observations when visiting the location. The source of informants in this research is the Management of the Kopu Raftimg Tourist Attraction. In this research, the data collection techniques used are observation, interviews and documentation. The results of this research reveal the implementation of Digital Marketing at the Kopu Rafting Object according to indicators, namely creating interesting content, sharing content, building relationships with visitors and building an online community. Keywords: Digital Marketing, Social Media, Tourist Attractions, Kopu Raftin